Audible Obstacle Warning System for Visually Impaired Person Based on Image Processing - Andik Yulianto; Ni'matul Ma'muriyah; Lina Lina (JURNAL NASIONAL TEKNIK ELEKTRO, 2023)
To be able to do their daily activities, a visually impaired person needs a guidance device to help him/her walk including to avoid obstacles on their way to the destination. The quick and clear instruction is given to the user is the most challenging problem to be solved. The visually impaired person should have simple guidance about the obstruction in front of him/her. Most guidance devices use simple sounds to give the warning without information about which direction the user should go. In this paper, an obstacle warning system based on image processing methods was developed. A guidance device for visually impaired persons using a single-board computer based on an image-processing algorithm has been designed. The main sensor of the guidance device is a NoIR camera. The distance measurement approximation model was developed with errors up to 4.3%. The test found that the proposed system can detect obstruction in the form of a person, the device also detects the stairs. The best detection obtains when the object position is less than 300 cm in front of the user.  The stair detection was carried out by using the Hough line transform method. The output of the system is the sound of direction that can be heard through the headset.